A functional SNP in the 3′‐UTR of TAP2 gene interacts with microRNA hsa‐miR‐1270 to suppress the gene expression. (5th December 2017) - Knox, Bridgett; Wang, Yong; Rogers, Lora J.; Xuan, Jiekun; Yu, Dianke; Guan, Huaijin; Chen, Jiwei; Shi, Tieliu; Ning, Baitang; Kadlubar, Susan A.
Abstract : The transporter associated with antigen processing 2 (TAP2) is involved in the development of multidrug resistance and the etiology of immunological diseases. In this study, we investigated whether the expression of TAP2 can be perturbed by single nucleotide polymorphisms (SNPs) located in 3′‐untranslated region (3′‐UTR) of the gene via interactions with microRNAs. Using a series of in silico assays, we selected the candidate microRNAs (miRNAs) with the potential to interact with functional SNPs of TAP2. The SNP rs241456—located in the 3′‐UTR of TAP2—resides in a potential binding site for hsa‐miR‐1270 and hsa‐miR‐620. HEK 293 cells, from a human kidney cell line, were used to characterize the extent of binding of miRNAs to each polymorphic allele of the SNP by a luciferase reporter gene assay. RNA electrophoretic mobility shift assays were used to evaluate the interaction between the miRNAs and each allele sequence of the SNP. We found that hsa‐miR‐1270 inhibited luciferase activity by binding to the T allele of the SNP in an allele‐specific manner. A negative correlation was also found between the expression of hsa‐miR‐1270 and the T allele of the SNP in kidney tissues. Our findings support the hypothesis that hsa‐miR‐1270 suppresses the production of TAP2 by binding to this SNP in the 3′‐UTR of this gene. Environ. Mol. Mutagen. 59:134–143, 2018. Published 2017. This article is a U.S. Government work and is in the public domain in the USA.